2023
DOI: 10.1007/s13311-022-01303-x
|View full text |Cite
|
Sign up to set email alerts
|

Better Fields or Currents? A Head-to-Head Comparison of Transcranial Magnetic (rTMS) Versus Direct Current Stimulation (tDCS) for Neuropathic Pain

Abstract: While high-frequency transcranial magnetic stimulation (HF-rTMS) is now included in the armamentarium to treat chronic neuropathic pain (NP), direct-current anodal stimulation (a-tDCS) to the same cortical targets may represent a valuable alternative in terms of feasibility and cost. Here we performed a head-to-head, randomized, single-blinded, cross-over comparison of HF-rTMS versus a-tDCS over the motor cortex in 56 patients with drug-resistant NP, who received 5 daily sessions of each procedure, with a wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In a first head‐to‐head trial, while 10 Hz rTMS to M1 relieved peripheral neuropathic pain due to radiculopathy, anodal tDCS proved not better than sham stimulation (Attal et al, 2016). Two larger and cross‐over head‐to‐head trials, however, showed that both tDCS and rTMS could relieve neuropathic pain to comparable levels, with only a slight superiority of rTMS in the reported amount of pain relief (André‐Obadia et al, 2023; Bonifácio de Assis et al, 2022). In these two studies, responders to one technique were not necessarily responders to the other, probably due to the different mechanisms driving pain relief in each of them; the corollary being that both modalities probably deserve to be tested before declaring a patient as unresponsive to cortical neuromodulation (e.g.…”
Section: Changing Stimulation Modality Without Changing Brain Targetsmentioning
confidence: 99%
“…In a first head‐to‐head trial, while 10 Hz rTMS to M1 relieved peripheral neuropathic pain due to radiculopathy, anodal tDCS proved not better than sham stimulation (Attal et al, 2016). Two larger and cross‐over head‐to‐head trials, however, showed that both tDCS and rTMS could relieve neuropathic pain to comparable levels, with only a slight superiority of rTMS in the reported amount of pain relief (André‐Obadia et al, 2023; Bonifácio de Assis et al, 2022). In these two studies, responders to one technique were not necessarily responders to the other, probably due to the different mechanisms driving pain relief in each of them; the corollary being that both modalities probably deserve to be tested before declaring a patient as unresponsive to cortical neuromodulation (e.g.…”
Section: Changing Stimulation Modality Without Changing Brain Targetsmentioning
confidence: 99%
“…Te results of this study are comparable to those of a previous network metaanalysis that showed that the pain score of the rTMS group was signifcantly lower than that of the control group (SMD: −0.92, 95% CI: −1.56 to −0.28; P � 0.01), while that of the tDCS group was not (SMD: −0.70, 95% CI: −1.45 to 0.04; P � 0.06). Moreover, a recent head-to-head randomized trial showed that rTMS was superior to tDCS in improving neuropathic pain [51,52]. Te advantage of rTMS compared to tDCS and CES results from a higher intensity with a more focused electrical feld [53].…”
Section: Discussionmentioning
confidence: 99%
“…One study contrasting their effects in patients with lumbosacral radiculopathy reported rTMS superiority 127 . However, patients unresponsive to conventional rTMS can also be alleviated by subsequent tDCS 128 , and two recent cross-over head-to-head trials in different neuropathic pain conditions reported similar global efficacy but a different subset of responding patients to each technique 129▪,130▪▪ . The use of tDCS as an add-on therapy to invasive procedures was recently reported in a small ( n =16) randomised study, where combining tDCS with dorsal root ganglion (DRG) stimulation provided better results than DRG alone 131▪ .…”
Section: Transcranial Direct-current Stimulationmentioning
confidence: 99%